Stem Cell Fate and Immunomodulation Promote Bone Regeneration via Composite Bio-Oss®/AviteneTM Biomaterial - Iaquinta, Maria Rosa; Martini, Fernanda; D’Agostino, Antonio; Trevisiol, Lorenzo; Bersani, Massimo; Torreggiani, Elena; Tognon, Mauro; Rotondo, John Charles; Mazzoni, Elisa (Frontiers in Bioengineering and Biotechnology, 2022)
Bone defects in maxillofacial regions lead to noticeable deformity and dysfunctions. Therefore, the use of biomaterials/scaffolds for maxillofacial bone regrowth has been attracting great interest from many surgical specialties and experts. Many approaches have been devised in order to create an optimal bone scaffold capable of achieving desirable degrees of bone integration and osteogenesis. Osteogenesis represents a complex physiological process involving multiple cooperating systems. A tight relationship between the immune and skeletal systems has lately been established using the concept of "osteoimmunology," since various molecules, particularly those regulating immunological and inflammatory processes, are shared. Inflammatory mediators are now being implicated in bone remodeling, according to new scientific data. In this study, a profiler PCR array was employed to evaluate the expression of cytokines and chemokines in human adipose derived-mesenchymal stem cells (hASCs) cultured on porous hydroxylapatite (HA)/Collagen derived Bio-Oss®/Avitene scaffolds, at up to day 21. In hASCs grown on the Bio-Oss®/Avitene biomaterial, 12 differentially expressed genes (DEGs) were found to be up-regulated, together with 12 DEG down-regulated. Chemokine CCL2, which affects bone metabolism, tested down-regulated. Interestingly, the Bio-Oss®/Avitene induced the down-regulation of pro-inflammatory inter-leukin IL-6. In conclusion, our investigation carried out on the Bio-Oss®/Avitene scaffold indicates that it could be successfully employed in maxillofacial surgery. Indeed, this composite material has the advantage of being customized on the basis of the individual patients favoring a novel personalized medicine approach.